Failure to use routine prevention of disability (POD) assessment resulting In permanent disability - Zoulba, Erika; Sjamsoe, Emmy Soedarmi; Menaldi, Sri Linuwih; Marissa, Melani; Irawan, Yudo (UI Scholars Hub, 2016)
Disability is one of problems in leprosy or Morbus Hansen (MH), which can cause the patient loose his autonomy and may affect his social relationship with family and community. Disability occurs due to neurological inflammation that can manifest as silent neuritis (which develops without any pain). Silent neuritis can be recognized early with a routine prevention of disability (POD) assessment. A 19-year-old male patient was referred from a District General Hospital with a history of numbness and stiffness of his 4th and 5th fingers of his left hand since 1 month before admittance. The patient was refered by Community Health Center (CHC or PUSKESMAS) after a one year treatment and RFT. During his treatment at the CHC, no assessment of peripheral nerve or POD had ever been performed. The POD assessment at our hospital demonstrated sensory deficit at some points of assessment on both palms and reduced muscle strength of the first and 5th fingers in both hands. Nerve conduction velocity (NCV) performed at the outpatient of Neurology Department, showed multiple mononeuropathy MH with irreversible damage. Nerve damage is still considered reversible when it occurs less than 6 months. In this case, the silent neuritis was not detected early and there was delayed treatment; as showed by NCV which revealed a manifestation of irreversible nerve damage. Routine POD assessment may detect the condition and appropriate treatment may overcome the nerve damage.